Unethical behaviour in higher learning institutions - Nurul Khair, Ishak (Universiti Malaysia Pahang, 2018)
Unethical behavior is an action that falls outside of what is considered morally right or proper for a person. Higher learning institutions are also facing the problem of unethical behavior or misconduct, and it can involve the students, lecturers or university administrators. This paper provides some insights into the issues of unethical behavior in higher learning institutions in Malaysia. It also identified types of unethical behavior among lecturers. It then discusses importance of ethical leadership in shaping the ethical conduct in higher learning institutions.